Circadian Rhythms in Adipose Tissue Physiology. Issue 2 (16th March 2017) - Kiehn, Jana‐Thabea; Tsang, Anthony H.; Heyde, Isabel; Leinweber, Brinja; Kolbe, Isa; Leliavski, Alexei; Oster, Henrik
ABSTRACT: The different types of adipose tissues fulfill a wide range of biological functions—from energy storage to hormone secretion and thermogenesis—many of which show pronounced variations over the course of the day. Such 24‐h rhythms in physiology and behavior are coordinated by endogenous circadian clocks found in all tissues and cells, including adipocytes. At the molecular level, these clocks are based on interlocked transcriptional‐translational feedback loops comprised of a set of clock genes/proteins. Tissue‐specific clock‐controlled transcriptional programs translate time‐of‐day information into physiologically relevant signals. In adipose tissues, clock gene control has been documented for adipocyte proliferation and differentiation, lipid metabolism as well as endocrine function and other adipose oscillations are under control of systemic signals tied to endocrine, neuronal, or behavioral rhythms. Circadian rhythm disruption, for example, by night shift work or through genetic alterations, is associated with changes in adipocyte metabolism and hormone secretion. At the same time, adipose metabolic state feeds back to central and peripheral clocks, adjusting behavioral and physiological rhythms. In this overview article, we summarize our current knowledge about the crosstalk between circadian clocks and energy metabolism with a focus on adipose physiology. © 2017 American Physiological Society. Compr Physiol 7:383‐427, 2017.